Inhibitory effect of bovine milk osteopontin on the initial attachment of Streptococcus mutans - Hisako Ishizuka; Kazuna Ishihara; Hideo Yonezawa; Kazuyuki Ishihara; Takashi Muramatsu (JDS Communications)
We investigated the effect of bovine milk osteopontin (OPN) on the initial adhesion of Streptococcus mutans to hydroxyapatite. Hydroxyapatite pellets were immersed in a 5.4 µM OPN solution at 37°C for 30 min. As a control, Milli-Q water was used. Streptococcus mutans were incubated at 37°C for 2 h on the pellets. Crystal violet staining and the quantitation of DNA were evaluated. Violet staining was observed on the hydroxyapatite pellets in the control group, but faint staining was seen in the OPN group. The amount of DNA attached to the hydroxyapatite pellet was significantly lower in the OPN group. These results suggest that initial adhesion of S. mutans to the hydroxyapatite is inhibited with OPN.